Analysis of The Meaning of Comparison and Contrast Figures in the Song Shiawase Album Love Story by Back Number - Rike Widia Dinanda; Ayu Putri Seruni (Universitas Cokroaminoto Palopo, 2026)
This research analyzes the figures of speech, specifically comparison and contrast, in the song